2020
DOI: 10.1186/s12884-020-2800-y
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil patient-controlled versus epidural analgesia on intrapartum maternal fever: a systematic review and meta-analysis

Abstract: Background: Intravenous remifentanil patient-controlled analgesia (RPCA) is an alternative for epidural analgesia (EA) in labor pain relief. However, it remains unknown whether RPCA is superior to EA in decreasing the risk of intrapartum maternal fever during labor. Methods: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic review and meta-analysis was performed by searching PubMed, EMBASE and the Cochrane Central Register of Controlled Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In theory, the mode of PCA can make the blood concentration of remifentanil synchronize with the uterine contractions [31]. Some studies [32][33][34] have shown that selfcontrolled intravenous administration of remifentanil can effectively relieve uterine contraction pain, and compound background doses can reduce the number of compressions, improve analgesia satisfaction, have little effect on the labor process, and do not increase the rate of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the mode of PCA can make the blood concentration of remifentanil synchronize with the uterine contractions [31]. Some studies [32][33][34] have shown that selfcontrolled intravenous administration of remifentanil can effectively relieve uterine contraction pain, and compound background doses can reduce the number of compressions, improve analgesia satisfaction, have little effect on the labor process, and do not increase the rate of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Lu et al reported a significantly higher risk of respiratory depression with Remifentanil PCIA as compared to epidural analgesia (RR: 2.86 (1.65-4.96), p= 0.0002). (22) In 2021, Zhang et al reported also an increased risk of maternal oxygen desaturation with Remifentanil PCIA as compared to epidural analgesia (RR= 3.23, 95% CI 1.98-5.30). 18 In addition, several case reports have described respiratory arrest and cardiac arrest in patients using Remifentanil PCIA for labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…32 In another 2017 randomized trial, Logtenberg et al did not find any difference in the incidence of maternal fever between Remifentail PCIA (10%) and epidural analgesia (8%) 33 In a 2020 meta-analysis including 6 randomized controlled trial and 3341 patients, Lu et al concluded that there is no solid evidence to illustrate that intrapartum maternal fever is lower with Remifentanil PCIA than with epidural analgesia. 22 Risks of decreasing epidural rate An increased use of alternative analgesia such as Remifentanil PCIA might carry the risk of an increased use of general anesthesia for intrapartum cesarean section or other obstetrical indications. This is particularly true for high-risk parturients such as patients undergoing a trial of labor after C-Section, obese patients and preeclamptic patients for whom epidural analgesia is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severe pain caused by the regular contraction of the uterus and the long labour process, many pregnant women are afraid of natural delivery. It is reported that labour pain can cause maternal sympathetic excitement and increase the release of catecholamines in the body, which inhibits uterine contraction, prolongs the labour process, causes an acid-base imbalance, decreases uterine blood flow and causes fetal distress [20][21][22]. For pregnant women, especially primiparas, childbirth pain causes strong psychological and physiological stress responses, resulting in slower expansion of the uterine orifice and a prolonged labour process, which makes it difficult to deliver smoothly [23].…”
Section: Vr Technology Combined With Moderate Perineal Protection Can...mentioning
confidence: 99%